The Use of Online Games and Aggressive Behavior in Adolescents: A Correlational Analysis of High School Students in Padangsidimpuan - Malim Soleh Rambe; Azijah Tussolihah Siregar; Laila Kalsum Hasibuan (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the relationship between online game use and aggressive behavior among 11th grade students at SMA Negeri 4 Padangsidimpuan in the 2024/2025 academic year. The method used was quantitative correlational with purposive sampling techniques and involved 27 students who met the criteria for intensive online game use. The research instruments were tested for validity and reliability, with Cronbach's Alpha values for each variable showing reliable categories. Analysis using Pearson's correlation yielded a value of r = –0.030 with a significance of 0.881, indicating that there was no significant relationship between online game use and aggressive behavior. These findings are not in line with a number of previous studies that show a significant influence of violent video games on adolescent aggression, suggesting that contextual factors such as school, type of game, and self-control may moderate this relationship. The implications of this study emphasize the need for schools to develop digital literacy programs, strengthen self-control, and provide psychological counseling to minimize the risk of aggressive behavior. Keywords: online games, aggressive behavior, adolescents, addiction, digital behavior